Effectiveness of Leadership in Managing Religious-Based Educational Institutions - Muh Habibulloh; Muh Ibnu Sholeh; Fakhruddin Al Farisy; Moh Nasihuddin; Himad Ali (International Journal of Education Management and Religion, 2025)
This study discusses the effectiveness of leadership in managing religious-based educational institutions, emphasizing the role of leaders in building vision, adopting transformational leadership styles, and their ability to manage conflicts and adapt to changes. In religious-based institutions, effective leadership relies not only on managerial skills but also on the integration of religious values in decision-making. The study uses a library research approach by analyzing various relevant literatures. The results show that visionary leadership provides clear direction for institutional development, transformational leadership enhances staff motivation and performance, while adaptive capability enables institutions to remain relevant in facing globalization and technological challenges. Additionally, conflict management based on religious values becomes a crucial aspect in creating organizational harmony. These findings contribute both theoretically and practically to the management of religious-based educational institutions, aiming for sustainability and improved educational quality.